2013
DOI: 10.1152/jn.00866.2012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for reticulospinal contributions to coordinated finger movements in humans

Abstract: The reticulospinal tract was recently shown to have synaptic connections to the intrinsic muscles of the fingers in nonhuman primates, indicating it may contribute to hand function long thought to be controlled exclusively through corticospinal pathways. Our objective was to obtain evidence supporting the hypothesis that these same anatomical connections exist in humans. startReact, an involuntary release of a planned movement via the startle reflex, provides a noninvasive means to examine the reticulospinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
128
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 57 publications
15
128
1
Order By: Relevance
“…This pattern mirrors the predominant recovery of upper extremity flexor function as observed in patients with corticospinal lesions such as stroke. The gain in reticulospinal output to forearm flexors in stroke patients is also supported by a recent study that showed normal StartReact responses in stroke patients during elbow flexion, whereas excessive flexor activity was seen in SAS trials involving elbow extension (Honeycutt and Perreault, 2012).…”
Section: Role Of Subcortical Structures In Motor Preparationmentioning
confidence: 56%
See 2 more Smart Citations
“…This pattern mirrors the predominant recovery of upper extremity flexor function as observed in patients with corticospinal lesions such as stroke. The gain in reticulospinal output to forearm flexors in stroke patients is also supported by a recent study that showed normal StartReact responses in stroke patients during elbow flexion, whereas excessive flexor activity was seen in SAS trials involving elbow extension (Honeycutt and Perreault, 2012).…”
Section: Role Of Subcortical Structures In Motor Preparationmentioning
confidence: 56%
“…The extent to which the reticular system is involved in motor preparation probably varies depending on the type of movement. It has been hypothesized that the reticular system is involved in grasping, but not in all tasks that require individuated finger movements (Honeycutt et al, 2013). Accordingly, the StartReact effect was absent in the first dorsal interosseous (FDI) muscle during index finger abduction, whereas a startle did accelerate FDI latencies during grasping (Honeycutt et al, 2013).…”
Section: Role Of Subcortical Structures In Motor Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is likely that both reticulospinal and corticospinal tracts are involved in a synergistic manner for all movements, movements more heavily dependent upon the corticospinal system would be less likely to show a reduction in reaction time in response to a SAS, if the StartReact effect is being mediated through a subcortical triggering mechanism. Indeed, both Carlsen et al (2009) and Honeycutt et al (2013) found a typical StartReact effect for the more reticulospinal based movements; however in the finger abduction task there was little if any reduction in PMT on startle trials when a startle response was observed in the sternocleidomastoid (SCM+) as compared to when no startle indicator was observed (SCM−), which the authors argued was due to the cortically-dependent nature of the task. Additionally, deep brain stimulation of the pedunculopontine nucleus has been shown to restore the StartReact effect in Parkinson’s disease patients (Thevathasan et al, 2011), suggesting subcortical involvement in the release of a prepared movement.…”
Section: Introductionmentioning
confidence: 98%
“…A total of 202 nonstartle testing trials were repeated (out of 1,200 total, 16.8%), of which 32 resulted in a second bad trial and were not repeated. We excluded 18 startle trials (out of 240 total, 7.5%) due to a lack of detectable startle reflexive response in the SCM (see Carlsen et al, 2011 for additional details); however, all remaining startle trials were included in the analyses as we were 1 Although key-press tasks are often performed using fingers, we chose a wrist movement due to previous research showing that finger movements do not show the same response triggering effects as wrist or grasp move ments in response to a startling stimulus (Carlsen, Chua, Inglis, Sanderson, & Franks, 2009;Honeycutt, Kharouta, & Perreault, 2013).2 Time intervals were chosen based on previous work examining key press durations and IRls (Klapp, 1995), ensuring movements required some form of timing (rather than moving as fast as possible) yet total movement time was short enough that online preparation would be dis couraged. RESPONSE TIMING CONTROL 2009 interested in how the SAS affected timing performance.…”
mentioning
confidence: 99%